Experimental short-time wildfire simulation—Physicochemical changes of forest mucky topsoil - Kupka, Dawid; Khan, Muhammad Owais; Kwika, Agata; Słowik-Opoka, Ewa; Klamerus-Iwan, Anna (Frontiers in Forests and Global Change, 2022)
Today, fires constitute one of the most important factors that can affect soil properties, acting at a rapid pace and on a large scale. They often result from climate change. The present study was aimed at examining how water capacity as well as carbon and nitrogen concentration change during a simulated fire of forest mucky soil under laboratory conditions. The combustion was carried out in two short-time variants – for 3 and 9 minutes. The results presented herewith show that even a short-term fire of the soil cover contributes to visible changes in the physicochemical parameters of the soil. Thermal decomposition of organic matter caused an increase in total carbon and nitrogen concentrations and a slight increase in the Ct/Nt ratio. The burning of soil samples caused a slight upward trend in soil pH and this was associated with SOM deprotonation. The experiment showed the effect of mucky soil burning on the change of its water relations. The three-minute combustion significantly increased the maximum water storage capacity (both after 4 and after 24 hours of immersion in water), while the nine-minute combustion showed significantly worse results. In order to better understand the impact of fires, among other things, on the hydrological properties of the forest floor, further research is needed, taking into account the quantity and the quality of organic matter.